Taking on the Yankees : Winning and losing in the business of baseball, 1903-2003 - Fetter, Henry D. (New York, N.Y. : W.W. Norton & Company, 2003)
"Based on extensive research in original sources, Taking on the Yankees focuses on the off-field circumstances - the management strategies, economic forces, social changes, and political and legal pressures - that played a decisive role in the Yankees' success on the diamond. The continuing contest for baseball supremacy is, in turn, placed in the context of the sport's own struggle to respond to a succession of social, economic, and legal challenges mounted by an ever-changing society." "The result is a perspective on baseball's past century and an unconventional examination of the often-misunderstood relationship between business and sports
Includes bibliographical references (p. 401-439) and index.
Keywords: New York Yankees; Baseball